2015
DOI: 10.1186/s12884-015-0622-0
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth among the hmong, other Asian subgroups and non-hispanic whites in California

Abstract: BackgroundWe investigated very preterm (VPTB) and preterm birth (PTB) risk among Hmong women relative to non-Hispanic whites and other Asian subgroups. We also examined the maternal education health gradient across subgroups.MethodsCalifornia birth record data (2002–2004) were used to analyze 568,652 singleton births to white and Asian women. Pearson Chi-square and logistic regression were used to assess variation in maternal characteristics and VPTB/PTB risk by subgroup.ResultsWhite, Chinese, Japanese, Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Consistent with our data, heterogeneity in preterm birth risk within the Asian American community based on maternal age and specific ethnic subgroup has precedent in the literature 5,13 . Vang et al posited that multivariate risk models for preterm birth should encompass more than maternal sociodemographic characteristics and prenatal care, as these variables alone may not synthesize the complexity of environmental stressors that Asian American mothers may be exposed to in the United States 21 . For example, structural discrimination and socioeconomic barriers to care can adversely influence pregnancy outcomes 22…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with our data, heterogeneity in preterm birth risk within the Asian American community based on maternal age and specific ethnic subgroup has precedent in the literature 5,13 . Vang et al posited that multivariate risk models for preterm birth should encompass more than maternal sociodemographic characteristics and prenatal care, as these variables alone may not synthesize the complexity of environmental stressors that Asian American mothers may be exposed to in the United States 21 . For example, structural discrimination and socioeconomic barriers to care can adversely influence pregnancy outcomes 22…”
Section: Discussionsupporting
confidence: 83%
“…Considering that nearly 1 in 10 births are preterm deliveries, representing about 400,000 PTBs in 2016, it is important to understand the potential causes and risk factors for PTB to prevent the mortality and morbidity outcomes that occur due to preterm deliveries ( Martin et al, 2018 ). Risk factors identified include previous preterm delivery, cigarette smoking, gestational diabetes and preeclampsia, maternal age, and socioeconomic status ( Cripe et al, 2012 ; Fuchs et al, 2018 ; Gibbs et al, 2012 ; Hedderson, 2003 ; Kyrklund-Blomberg & Cnattingius, 1998 ; Mercer et al, 1999 ; Smith et al, 2007 ; Thompson, 2002 ; Vang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reported that Filipinas had higher incidence rates (12.62), while Rao et al (2006) reported that Vietnamese had a higher incidence rate (12.4) of preterm delivery less than 32 weeks [ 83 , 85 ]. However, one generally consistent finding across the studies was that the rates of preterm deliveries were lower in East Asian American subgroups (Chinese, Japanese, and Korean) than in other subgroups [ 82 , 83 , 85 , 86 ]. See Table 7 for incidence rates.…”
Section: Introductionmentioning
confidence: 78%
“…Five articles included pregnancy-associated hypertension, preeclampsia, and/or eclampsia [ 82 , 83 ]. Two included incidence rates for preeclampsia for the Indian/Pakistani, Japanese, Chinese, Filipina, Korean, and Vietnamese subgroups, and one study included prevalence rates for Cambodian, Lao, Vietnamese, and Japanese females [ 84 86 ]. The five studies indicated that Filipina women had the highest incidences of PAH (2.86; 6.3), preeclampsia (6.8; 1.5), and eclampsia (0.19) of all the Asian subgroups considered (See Table 7 for incidence comparison).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation